The Effectiveness of Entrepreneurship Education on Students’ Self-Efficacy and Entrepreneurial Intention: A Comparative Study of Major Cities in Indonesia - Soelaiman, Lydiawati; Keni, Keni; Chin, Tay Lee (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
Objective: Entrepreneurship has become a strategic solution to address unemployment in Indonesia, where the entrepreneurial ration remains relatively low at only 3.47%. This study investigates the role of entrepreneurship education in enhancing students’ entrepreneurial self-efficacy and entrepreneurial intention within the context of higher education in Indonesian. Method: Using quantitative approach, this study utilizes PLS-SEM to examine relationship among constructs, while PLS-MGA was used to assess regional differences across. Samples consist of 537 undergraduate students who had participated in entrepreneurship education programs at excellent-status higher education institutions in Jakarta, Bandung, and Surabaya, selected through purposive sampling.  Results:  The result reveals that entrepreneurial education has a significant effect on both entrepreneurial intention and entrepreneurial self-efficacy. Furthermore, entrepreneurial self-efficacy partially mediates the relationship between entrepreneurship education and entrepreneurial intention. The MGA results show no significant differences across the three cities, except for the effect of entrepreneurship education on self-efficacy between Jakarta and Surabaya.  Novelty: Overall, the findings suggest relatively consistent effects of entrepreneurship education across major urban areas in Java. This study provides practical implication for developing experience-based entrepreneurship programs in HEIs.